2018
DOI: 10.5194/amt-11-5153-2018
|View full text |Cite
|
Sign up to set email alerts
|

Constructing a precipitable water vapor map from regional GNSS network observations without collocated meteorological data for weather forecasting

Abstract: Abstract. Surface pressure (Ps) and weighted mean temperature (Tm) are two necessary variables for the accurate retrieval of precipitable water vapor (PWV) from Global Navigation Satellite System (GNSS) zenith total delay (ZTD) estimates. The lack of Ps or Tm information is a concern for those GNSS sites that are not collocated with meteorological sensors. This paper investigates an alternative method of inferring accurate Ps and Tm at the GNSS station using nearby synoptic observations. Ps and Tm obtained at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…The observed reflectance of the top of atmosphere is corrected by gas absorption at visible to near‐infrared channels. A gas correction was implemented for water vapor and ozone (Yoshida et al, ), because their amount varies significantly with location and time (Chen et al, ). Surface reflectance is an essential parameter for building lookup tables (LUTs).…”
Section: Himawari‐8/ahi Aerosol Retrievalmentioning
confidence: 99%
“…The observed reflectance of the top of atmosphere is corrected by gas absorption at visible to near‐infrared channels. A gas correction was implemented for water vapor and ozone (Yoshida et al, ), because their amount varies significantly with location and time (Chen et al, ). Surface reflectance is an essential parameter for building lookup tables (LUTs).…”
Section: Himawari‐8/ahi Aerosol Retrievalmentioning
confidence: 99%
“…The latest studies (e.g., [19,20]) have shown that GNSS-derived PWV has considerable potential applications in precipitation forecasting or meteorological disaster warning. Furthermore, the analysis of water vapor changing trends or the forecasting of short-term precipitation events requires the transformation of one-dimensional PWV data from observation networks to two-dimensional data through spatial interpolation [21]. The spatial interpolation algorithm consists of showing the dynamic distribution for water vapor within the CORS coverage area by real-time processing the GNSS-derived PWV of each receiver in the CORS network.…”
Section: Introductionmentioning
confidence: 99%
“…A linear relationship exists between Tm and height [36], [37], (10) can be used to characterize the vertical dependence of Tm, namely the Tm lapse rate:…”
Section: Radiosonde Data Estimation Of the Tm Lapse Ratementioning
confidence: 99%
“…Zhang et al [36] explored the Tm lapse rate in China using the ERA-Interim data set over a whole year period and demonstrated that the accuracy of Tm estimated was improved with the Tm lapse rate in China areas. Chen et al [37] estimated the Tm lapse rate in some synoptic sites in Hunan Province of China to obtain the more accurate PWV maps. However, the Tm lapse rate was only mentioned briefly but not in depth, or just researched regionally in the previous literatures.…”
Section: Introductionmentioning
confidence: 99%